Profiles of Mobile Phone Problem Use in Bullying and Cyberbullying Among Adolescents - Méndez, Inmaculada; Jorquera Hernández, Ana Belén; Ruiz-Esteban, Cecilia (Frontiers in Psychology, 2020)
Technology is being used by individuals of all ages; young children show a high tendency of problematic use of devices such as smartphones. This study aimed to identify different profiles that vary in conflicts related to problematic mobile phone use and maladaptive communication and emotional patterns. Therefore, we examined whether there are significant differences in bullying and cyberbullying among teenagers who have a problem utilizing mobile phones. The study participants were 810 students of Compulsory Secondary Education (M = 13.99, Sd = 1.32), with 52.2% being girls. Questionnaires on school violence and experiences related to mobile phones were administered. The latent profile analysis identified three different types of problematic mobile phone use: a) low levels of conflict was associated with mobile phone abuse and low levels of communication and emotional use; b) moderate levels of conflict was associated with mobile phone abuse and moderate levels of communication and emotional use; and c) high levels of conflict was associated with mobile phone abuse and high levels of communication and emotional use. The study results highlight significant differences in the manifestations of school violence between the profiles. Finally, this study’s findings form the basis for the development of education programs to prevent mobile phone abuse and school violence and therefore academic adjustment.